Aquatic tardigrades in Poland – a review - Kayastha Pushpalata; Wiśniewska Joanna; Kuzdrowska Klaudia; Kaczmarek Łukasz (Limnological Review, 2021)
The diversity, distribution and ecology of aquatic Tardigrada in Poland remain poorly known. We reviewed the literature focused on tardigrades in Poland and recognized only 15 aquatic taxa which were reported from various freshwater and marine habitats. Among them, 12 are freshwater and three are marine taxa. Hypsibius dujardini is Poland’s most widely-distributed hygrophilous species, but it re presents rather a complex of cryptic species and their diagnosis requires integrative approaches. Most reports of aquatic tardigrades in Poland are accidental findings mostly from water bodies in Tatra Mountains or from lakes in Masurian Lake District. Some species were also reported from small ponds or wastewater treatment plants in other regions like Małopolska or Wielkopolska Provinces.